Contextualization of Islamic Law on Environmental Issues from the Perspective of Maqashid al-Sharia: Kontekstualisasi Hukum Islam tentang Isu Lingkungan Hidup dari Perspektif Maqashid al-Sharia - Muhammadong (CV Kalimasada Group, 2026)
This study takes the maqashid al-sharia as the perspective from which Islamic law addresses environmental issues. The research discusses three topics, namely: the response of Islamic law to environmental damage, the principles of maqashid al-sharia as a basis for environmental protection, and the implementation of Islamic laws in the current environmental life. The legal normative research is carried out by using a conceptual and literature study approach. The facts were obtained from Islamic law references, maqashid thought, environmental fiqh references and pertinent scientific studies. The findings indicate that environmental challenges involve moral, social and spiritual dimensions besides technical considerations. The second maqashid al-sharia is that the conservation of the environment is closely related to the conservation of religion, life, intellect, lineage and wealth. The damage to the environment may threaten the survival of human beings and may obstruct the rule of Allah’s creation. Therefore, the Islam law must be understood in its context so that it can tackle the contemporary environmental problems. In conclusion, maqashid al-sharia provides an excellent normative framework for the creation of Islamic legislation which is environmentally friendly, oriented towards the public good and conducive to human sustainability.